Improving the fluorescence brightness of naphthalimide and nitrobenzoxadiazole dyes with cycloalkylamine auxochromes - Das S.; Goswami P.; Indurthi H.K.; Koch B.; Sharma D.K. (My University, 2025)
We have installed cycloalkylamino auxochromes on naphthalimide (5a-5e) and nitrobenzoxadiazole (6a-6e) dyes. Their photophysical characterization revealed that the cyclobutylamino auxochrome in both dyes (5b and 6b) demonstrated high quantum yield and fluorescence brightness compared to their azetidine counterparts (5 and 6) in aqueous solution. The computational studies were performed to substantiate the experimental photophysical results. Cytotoxicity assay in breast adenocarcinoma (MDA-MB-231) and non-cancerous human embryonic kidney 293 (HEK-293) cells indicated significant biocompatibility of cyclobutylamino auxochrome. Moreover, cellular imaging and photostability experiments demonstrated the practical application of cycloalkylamino auxochromes. © 2024 Elsevier Ltd